大脳基底核のポジティビティ効果との関わり：言語処理における加齢変化 - 國見, 充展; 玉岡, 賀津雄; 木山, 幸子; リヌス, フェアドンスコット; 中井, 敏晴 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
Memorization is fundamental to human communication. However, many elderly experience memory decline with aging, which often hampers fluent communication. In order to facilitate elderlies' memory performance, positive emotions have been shown to have a beneficial effect. Particularly, elderly are more likely to retrieve positive memories compared to negative ones. However, the neural correlates of this bias has not yet been clarified within the language domain. We assessed the age-related changes concerning the role memory plays during emotional sentence processing, utilizing functional magnetic resonance imaging. A sentence judgment task and a subsequent surprise sentence recognition task were administered to 20 healthy young adults and 20 healthy elderly adults. Results of the analyses of covariance (ANCOVA) for the judgment task, using accuracy rate of the recognition task as a covariate, revealed that the elderly's accuracy rate for recognizing positive emotional sentences were correlated with their activity in the basal ganglia (BG) including the left lateral globus pallidus and the right putamen while processing positive sentences compared to neutral ones. Contrarily, such effect was not found for negative sentences.